2015
DOI: 10.1037/aca0000023
|View full text |Cite
|
Sign up to set email alerts
|

Art-elicited chills indicate states of being moved.

Abstract: Following suggestions by Benedek and Kaernbach (2011), we investigated the hypothesis that art-elicited chills might indicate emotional states of being moved. We focused on two prototypical variants of being moved: one involving sadness as a key component, and the other joy. Thirty participants watched 25 moving film excerpts of either the sadly or the joyfully moving type (e.g., farewell scenarios and reunion scenarios, respectively). They rated how sad, how joyful, and how moved they felt after each film cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
149
1
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 100 publications
(163 citation statements)
references
References 42 publications
11
149
1
2
Order By: Relevance
“…Mixed emotions can occur even during the same section of films and music4546. Already, some chills studies have suggested a positive relationship between chills and mixed emotions (happy and sad)63547. The current results found that the mixed emotion of chills was simultaneous pleasure, happiness, and sadness.…”
Section: Discussionsupporting
confidence: 52%
See 1 more Smart Citation
“…Mixed emotions can occur even during the same section of films and music4546. Already, some chills studies have suggested a positive relationship between chills and mixed emotions (happy and sad)63547. The current results found that the mixed emotion of chills was simultaneous pleasure, happiness, and sadness.…”
Section: Discussionsupporting
confidence: 52%
“…So far, research studies of peak emotion have mainly focused on the chills response63536 although Goldstein9 already suggested the existence of the tears response. Our main hypothesis was that tears would be psychophysiologically different from chills.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the initial positive correlation between sadness and beauty was fully mediated by movingness, and that movingness -rather than 845 beauty -also mediated the relationship between sadness and liking (see subsection 3.1 for a discussion on empathy and being moved). "Being moved" has been conceptualised both as an interpersonally significant emotion that activates (and is activated by) pro-social behaviour and the value of social bonds [47,139], as well as a pleasurable aesthetic emotion [200] often accompanied by 850 chills or frissons [201,202]. This dual nature of "being moved" suggests that percepts of beauty must conform with with prosocial norms and ideals, and that, in order to be experienced as beautiful, music may have to be perceived as conveying prosocial intentions [203].…”
Section: Aesthetic Appreciation and Beautymentioning
confidence: 99%
“…Discriminatory analyses further showed that moving can be equated with touching or deeply moving, but differs from exciting (which is higher in arousal level), elevating (which is more positive), and shattering (which is more negative, Menninghaus et al, 2015). When people are intensely moved, they may experience goose bumps, moist eyes, a lump in their throat, and/or a warm feeling in the chest (Benedek & Kaernbach, 2011;Scherer & Zentner, 2001;Schubert, Zickfeld, Seibt, & Fiske, in press;Strick, De Bruin, De Ruiter, & Jonkers, 2015;Wassiliwizky, Jacobsen, Heinrich, Schneiderbauer, & Menninghaus, 2017;Wassiliwizky, Wagner, & Jacobsen, 2015).…”
mentioning
confidence: 99%